From Symbol to Meaning: Philosophy of Bulungan Ornamental Motifs as Living Cultural Heritage in Arts Education - Muhlis Muhlis; Irwanto Irwanto; Muhammad Aulia Rahman Aulia Rahman; Sainal A (Vidya Karya, 2026)
This research examines the philosophy embedded in Bulungan ornamental motifs as a form of living cultural heritage in North Kalimantan. These motifs function not only as decorative elements but also as representations of values such as harmony, bravery, respect for nature, and reverence for ancestors. Employing a descriptive qualitative method, the study collected primary data through in-depth interviews with artisans, cultural leaders, teachers, and students, supported by purposively selected visual documentation from archival sources and field observations. The data were analyzed using thematic coding and visual content analysis to uncover symbolic meanings reflected in patterns, colors, and forms. The findings indicate that certain motifs, such as the dragon, signify protection of the Kayan River, whereas floral and plant motifs symbolize fertility and the continuity of life. Beyond their aesthetic function, these symbols act as markers of cultural identity and as valuable learning resources in art education, encouraging creativity, cultural awareness, and character formation. Overall, the study highlights how traditional artistic expressions operate both as philosophical representations and as educational instruments for preserving local wisdom.